2013
DOI: 10.1080/13032917.2013.777673
|View full text |Cite
|
Sign up to set email alerts
|

Electricity consumption and international tourism: the case of Singapore

Abstract: International inbound tourists consume electricity of a destination either directly or indirectly. Despite the recognition of potential effect of international tourism on electricity consumption, not many papers have investigated the existence of such relationship empirically. This research note intends to fill the existing literature gap by determining such relationship with time-varying volatility models using the data of Singapore. A GARCH-M(1,1) model is selected. This model indicates that industrial produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 8 publications
1
2
0
Order By: Relevance
“…From Granger Causality Test, the findings show that inbound tourism influences on energy demand. It is consistent with the study of Lee (2013). The study indicated that electricity demand impact on inbound visitors was positive because the facilities in hotel were required by electricity.…”
Section: Discussionsupporting
confidence: 90%
“…From Granger Causality Test, the findings show that inbound tourism influences on energy demand. It is consistent with the study of Lee (2013). The study indicated that electricity demand impact on inbound visitors was positive because the facilities in hotel were required by electricity.…”
Section: Discussionsupporting
confidence: 90%
“…The variable ELPC refers to the per capita electricity consumption measured in terms of kilowatt hours per capita. Since sufficient availability of electricity, particularly across the tourist spots, influences the travel decisions of the international tourists, it is pertinent to control for this key macroeconomic aggregate in modeling the IITD [2]. Thus, a positive association between electricity use and IITD can be anticipated.…”
Section: Empirical Model and Datamentioning
confidence: 99%
“…This can be understood from the statistical estimates that the International Inbound Tourism Demand (IITD), in terms of the number of tourist arrivals in South Asia, has surged by almost six-fold over the last decade or so [1]. Simultaneously, this growth in the IITD, to some extent, has also amplified the overall demand for energy across this region [2]. Therefore, the sustainability of international tourism influx into South Asia can be hypothesized to be influenced by the reliability of the energy supplies within the South Asian economies of concern.…”
Section: Introductionmentioning
confidence: 99%